2014
DOI: 10.1161/circulationaha.113.003734
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Fate Mapping in Mice With Pulmonary Hypertension

Abstract: Experimental models of pulmonary hypertension that have used combinations of chronic hypoxia, pneumonectomy, and endothelial injury by monocrotaline or the vascular endothelial growth factor receptor antagonist SUGEN 5416 have been reviewed. 9 Whereas models based on hypoxia demonstrateBackground-Pulmonary endothelial injury triggers a reparative program, which in susceptible individuals is characterized by neointima formation, vascular narrowing, and the development of pulmonary arterial hypertension. The neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 41 publications
2
81
0
1
Order By: Relevance
“…16,52 To gain insights into the mechanisms regulating this process, we found that the expression of primary cilia in the aorta of Westerntype diet fed LDLR −/− mice was restricted to nonaffected areas, characterized by PECAM-1-expressing ECs. On the contrary, primary cilia or PECAM-1 were not observed in ECs at SLUGpositive regions, suggesting a loss of the endothelial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…16,52 To gain insights into the mechanisms regulating this process, we found that the expression of primary cilia in the aorta of Westerntype diet fed LDLR −/− mice was restricted to nonaffected areas, characterized by PECAM-1-expressing ECs. On the contrary, primary cilia or PECAM-1 were not observed in ECs at SLUGpositive regions, suggesting a loss of the endothelial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although additional experiments are required to identify the involved factors, these findings clearly support the idea that pulmonary pericytes are a potential in situ source of SM-like cells that could contribute to PAH pulmonary vascular remodeling. Interestingly, Qiao et al 56 also recently demonstrated that the endothelial-to-mesenchymal transition is another mechanism contributing to SM hyperplasia in PAH. Activation of proteases intervenes in proteolytic processing of the extracellular matrix, with release of growth factors (FGF-2, TGF-β, vascular endothelial growth factor, and PDGF) stored in their heparin-like glycosaminoglycans, actively contributing to changes of the cellular microenvironment, which can also result in modification of the pericyte differentiation state.…”
Section: Ricard Et Al Pericytes In Pulmonary Arterial Hypertension 1593mentioning
confidence: 99%
“…It has recently been confirmed that EndMT is involved in CVDs such as PAH [22,23] and AS [3,4]. TGF-β1, a special multifunctional cytokine involved in the physiological and pathophysiological processes of the cardiovascular system, has been found to inhibit the vascular EC phenotype due to the disruption of endothelial intercellular junctions and the loss of apical-basolateral polarity [5,24].…”
Section: Discussionmentioning
confidence: 99%